APPLICATION OF THE PEER TUTOR METHOD TO IMPROVE FIQIH LEARNING OUTCOMES - Karwadi, Karwadi (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2023)
The purpose of this study was to improve students' activities and learning outcomes in fiqh subjects by applying the peer tutor method. This research is a class action research consisting of two cycles. The subjects of this study were third grade students of MI Matla'ul Atfal, totaling 27 students. Data collection techniques are done by giving tests and observations. Based on the results of the study, it shows that students are more active in learning activities in the classroom. Student learning outcomes also increased from each cycle. This can be proven by the completeness of student learning in cycle I as many as 17 students who are complete and 24 students who are complete in cycle II with a total of 27 students. Therefore, the application of peer tutors can improve student learning outcomes in fiqh learning.